Mathematical Study of Fractional Magnetohydrodynamic Blood Flow Nanofluid in Activation of Thermal Radiation with Wright Function (African Journal for Industrial and Applied Mathematics, 2025)
A study of magnetohydrodynamics model of blood flow is made withsingle walls carbon nanotubes, copper (Cu), tin $({\rm TiO}_2),$ and alumina $({\rm Al}_2{\rm O}_3)$ andCu as base nanoparticles through a circular cylinder. The fluid inside the tube isacted by an oscillating pressure gradient and an external constant magnetic field.The whole study is based on a mathematical model that includes Caputo fractional-order derivatives. Solutions for the blood velocitie, blood temperature distribution,and blood concentration distribution are obtained through the Laplace transformand expressed by the Wright function. Effects of the fractional-order parameter,magnetic field, the magnetic parameter $M,$ the Grashof numbers Gr and Gm, thedimensionless time $t,$ and the Prandtl parameter $Pr$ are addressed using numericalsimulations. Results show that the applied magnetic field reduces the velocities ofthe fluid and particles. However, under long time intervals, particles seem to be accelerated, but their velocity is suitably controlled by the fractional-order parameter.